Nas linhas do telemarketing: uma “chamada” à precarização e flexibilização da força de trabalho em Maceió - Silva, Bárbara Suellen Santos da (2017)
In the year of 2013, the State and municipal public power of Alagoas and Maceió, under the discourse of diversification of the economy, announced the opening of the first telemarketing company in the state. The following year, the same company opened its first operations unit in the capital, with initial 600 workers, most of them telemarketers. Still in the process of negotiation between the Italian company and the city Government, the representatives of the multinational already anticipated the announcement of the creation of 10 thousand jobs by the year 2015. Considering the development of the area of telemarketing in Brazil, we were interested the fact that this sector To complete its expansion in the Northeast region when settling in the Caetes lands, especially considering the social characteristics and composition of the state labor market. Thus, this research has the objective of analyzing the implications of this type of work, both for the labor force that occupies the ranks of that job and for the formal labor market in the city of Maceió. We take the Marxian assumptions of historicaldialectical materialism by thinking of our object as a synthesis of multiple determinations. With regard to changes in the world of work over the centuries, we bring a panorama of some phases of capitalism to a deeper understanding of the period of productive restructuring of capital and the social transformations arising from it, and to reach the particularity of Alagoas. In what is related to the analysis of the local labor force, we use the precariat category, as defined by the sociology of Brazilian work. Our research also presents the panorama of the telemarketing work universe in Brazil, in order to relate its characteristics to those verified in the city of Maceió and how its logic imbues with that of the political, social and economic functioning of the state. Finally, our analysis allows us to identify the formation of a young working class, in its first job, erected on a terrain of precariousness; As the aspects of political and class organization are rarefied, at the same time necessary in the face of this conjuncture; As this economic diversification, classified by the public power as necessary for social development, actually brings about the intensification of the precariousness of work in Maceió.